The technical-reasoning network is recruited when people observe others make or teach how to make tools: An fMRI study - Alexandre Bluet; Emanuelle Reynaud; Giovanni Federico; Chloé Bryche; Mathieu Lesourd; Arnaud Fournel; Franck Lamberton; Danielle Ibarrola; Yves Rossetti; François Osiurak (iScience)
Summary: Cumulative technological culture is defined as the increase in efficiency and complexity of tools over generations. The role of social cognitive skills in cultural transmission has been long acknowledged. However, recent accounts emphasized the importance of non-social cognitive skills during the social transmission of technical content with a focus on technical reasoning. Here, we contribute to this double process approach by reporting an fMRI study about the neurocognitive origins of social learning. Participants watched videos depicting tool-making episodes in three social-learning conditions: reverse engineering, observation, and teaching. Our results showed that the technical-reasoning network, centered around the area PF of the left inferior parietal cortex, was preferentially activated when watching tool-making episodes. Additionally, teaching elicited the right middle temporal gyrus. This study suggests that technical reasoning underpins technological culture, while social cognition enhances learners’ technical reasoning by guiding attention to key aspects of the technology.